ENGLISH WOMEN AT THE TURN OF THE 19TH CENTURY AS DEPICTED IN “PRIDE AND PREJUDICE’’ BY JANE AUSTEN = HÌNH ẢNH NGƯỜI PHỤ NỮ ANH NỬA ĐẦU THẾ KỶ XIX ĐƯỢC MIÊU TẢ TRONG TÁC PHẨM KIÊU HÃNH VÀ ĐỊNH KIẾN CỦA JANE AUSTEN - Vũ, Thị Thanh Hòa (2021)
As an attempt to contribute to gaining more insights into the fiction Pride and Prejudice by Jane Austen, this research aims to investigate the image of English women at the turn of 19th century depicted in the fiction. Specifically, the study focuses on the low status of women in marriage, inheritance and education. In addition, the reaction of those women, both supporters and opponents, was also meticulously analyzed. Beside the disapproval to prejudice at that time on feminine rights, Jane Austen successfully built her admirable image of women – Elizabeth Bennet. Indeed, the novel Pride and Prejudice helps the novelist express her criticism of social conventions against women at the turn of 19th century.